PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN PEMANFAATAN KAIN PERCA SEBAGAI AKSESORIS MELALUI MEDIA YOUTUBE DI LSM BENING SAGULING - Zakia, Tsaniatu (Comm-Edu (Community Education Journal), 2021)
AbstractThis research is motivated bye the large amount of spare time owned by housewives ehich has not been used optimally, but this free time is used to play smartphones. The purpose of this research is to describe in more detail about women's empowerment through training on the use of patchwork as accessories through Youtube media in Bening Saguling. This study uses a descriptive method with a qualitative approach, which is the subject of this study, one training Instructor and 10 housewives. While the data collection technique is by means of observation, interview and documentation. The result of this training is to provide patchwork skills for low-educated women, providing a skill that can be of personal use and of sale value. The benefits of this activity are that the work can be sold so that it is expected to be able to improve the standard of living of the community and fill women's spare time with more useful activities.